Manajemen Pembuangan Sampah Dalam Rangka Mendukung Smart City di Kota Baubau - Ihsyaluddin; Putriani; La Ode Rahman Daud (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
This study aims to determine how waste management and disposal problems are in Baubau City. The approach used in this study is a qualitative approach using analysis and presented descriptively qualitatively. Data collection using interview methods and secondary data. Waste management in Betoambari District has not been implemented optimally. Waste disposal management or management is problematic due to the lack of personnel in the field, the availability of waste transport vehicles, and the availability of budget. Which has an impact on the accumulation of waste, the distribution of uncontrolled piles of waste and low public awareness. Therefore, the need for government commitment in implementing established policies and encouraging budget availability, continuing to socialize and efforts to increase public awareness related to waste disposal behavior. So that Baubau City in order to become a smart city in the smart environment indicator has not met the criteria.